Hydrogen Gas Inhalation (4%) could Reduce Lung Inflammation and Blood Pressure in Rats with Monocrotaline-Induced Pulmonary Hypertension - Tatyana Kuropatkina; Dmitrii Atiakshin; Fedor Sychev; Marina Artemieva; Tatyana Samoilenko; Olga Gerasimova; Viktoria Shishkina; Khaydar Gufranov; Natalia Medvedeva; Tyler W. Le Baron; et al. (Medicine and Medical Research: New Perspectives Vol. 2, 2024)
The aim of this study was to investigate the effects of inhaling atmospheric air containing 4% hydrogen on the symptoms and progression of PH in male Wistar rats using the MCT-induced model. Interstitial lung diseases (IPD), associated with inflammatory processes and the appearance of fibrosis, lead to impaired ventilation-perfusion ratio and hypoxia. Recently, strategies and drug approaches for the treatment of IPD-associated pulmonary hypertension have been widely discussed. Hydrogen has been shown to exhibit selective antioxidant properties against hydroxyl radicals and exert antioxidant and anti-inflammatory effects. Because monocrotaline causes oxidative stress, the monocrotaline-induced model of pulmonary hypertension is appropriate for researching compounds having antioxidant properties. On day 1, male Wistar rats were subcutaneously injected with either a water-alcohol solution of monocrotaline or control solution consisting solely of water and alcohol. One group of monocrotaline-injected animals was placed in a plastic box continuously ventilated with atmospheric air containing 4% molecular hydrogen, while the two other groups (one injected with monocrotaline and the other with vehicle) were placed in boxes ventilated with atmospheric air. After 21 days, hemodynamic parameters were measured under urethane narcosis. The results showed that, although hydrogen inhalation had no effect on the main markers of pulmonary hypertension induced by monocrotaline injection, there was a reduction in systemic blood pressure due to its systolic component, and a decrease in TGF-\(β\) expression, as well as a reduction in tryptase-containing mast cells. The results in combination with previous published results indicate that molecular hydrogen may be a useful therapeutic agent to combat pulmonary hypertension. Further research with larger sample sizes and exploring different routes of administration, concentrations and durations is needed to determine the optimal therapeutic approach. Overall, these findings suggest that molecular hydrogen may hold promise as a therapeutic agent in the treatment of pulmonary hypertension, in patients but further investigation is warranted.